Healthcare System and Managerial Implications - Antonia Rosa Gurrieri; Marilene Lorizio (Research Highlights in Disease and Health Research Vol. 4, 2023)
The Covid-19 pandemic and the negative economic impact recorded in the last 3 years have highlighted the inefficiencies of the national health systems. The role of managers is crucial in addressing inefficiencies in healthcare and in proposing new business models. The aim of this work is to analyze the main inefficiencies that have emerged and to focus on managerial solutions.